2015
DOI: 10.1007/s10815-015-0554-7
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 and T1 gene polymorphisms in Brazilian women with endometriosis

Abstract: GSTM1 null genotype frequency was similar between cases and controls. The GSTT1 null genotype was more frequent in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The result for GSTM1 and GSTT1 deletion polymorphisms concerning the GSTM1*0/*0 and GSTT1*0/*0 genotype was 49% and 31%. This is an agreement with previous report of Kubiszeski et al [9] in Cuiabá population (50% and 32%) and Rocha et al [10] in Amazônia population. Other studies in the Brazilian population from Bahia, performed by Rocha et al [10] and Pinhel et al [11] in the population from São Paulo confirm our findings in the Goiânia population.…”
Section: Discussionsupporting
confidence: 94%
“…The result for GSTM1 and GSTT1 deletion polymorphisms concerning the GSTM1*0/*0 and GSTT1*0/*0 genotype was 49% and 31%. This is an agreement with previous report of Kubiszeski et al [9] in Cuiabá population (50% and 32%) and Rocha et al [10] in Amazônia population. Other studies in the Brazilian population from Bahia, performed by Rocha et al [10] and Pinhel et al [11] in the population from São Paulo confirm our findings in the Goiânia population.…”
Section: Discussionsupporting
confidence: 94%
“…Age groups did not impact DEHP serum levels. Controversy remains, as DEHP is broken down by glutathione S-transferase and P450 enzyme, which has been reported to be compromised in endometriosis patients [72]. This may explain the difference in serum concentration, as the control patients are able to metabolize DEHP into metabolites which were not recorded.…”
Section: Phthalate Estersmentioning
confidence: 99%
“…Of the 28 studies dealing with the glutathione S-transferase mu 1 (GSTM1) null genotype, 15 studies were included: 11 CAT1 studies (Babu et al 2005;Hadfield et al 2001;Hassani et al 2016;Huang et al 2010;Hur et al 2005;Kim et al 2007;Kubiszeski et al 2015;Roya, Baludu, and Reddy 2009;Vichi et al 2012) and four CAT2 studies (Arvanitis et al 2003;Baranova et al 1999;Wu et al 2012).…”
Section: Icam1 Genementioning
confidence: 99%
“…In contrast, five earlier studies concluded that the GSTT1 null genotype is associated with endometriosis susceptibility (Chen, Xu, et al 2015;Ding et al 2014;Guo 2005;Xin et al 2016;Zhu et al 2014). However, we included more recent data in the meta-analysis (including three case-control studies Kubiszeski et al 2015)), and excluded the CAT3 studies (Frare et al 2013;Lin et al 2003;Morizane et al 2004) and studies not published in English (Ding et al 2004;Ivashchenko et al 2003) that were taken into account in the earlier meta-analyses. However, it is clear that the selection of control participants influences the overall result, as discussed above for CYP17A1 rs743572, nor the disease stage for understanding the differences observed between the various meta-analyses.…”
Section: Accepted Manuscriptmentioning
confidence: 99%